Dukungan Keluarga dengan Kepatuhan Pengobatan Pasien Diabetes Mellitus Tipe 2 - Satriani Satriani; Ricky Riyanto Iksan; Pandan Enggarwati; Wiwie Herdalisah; Elfira Awalia Rahmawati (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aimed to determine the relationship between family support and medication adherence in patients with Type 2 Diabetes Mellitus. The research method used was a quantitative study with a cross-sectional design. The results showed a significant relationship between family support and medication adherence (p-value = 0.001), with patients receiving good family support tending to have higher levels of medication adherence. In conclusion, family support is significantly associated with medication adherence in patients with Type 2 Diabetes Mellitus. Keywords: Family Support, Type 2 Diabetes Mellitus, Medication Adherence